Particulate Filled Polymer Electrolyte Membrane for Fuel Cell Applications - Banerjee, Soma; K. Kar, Kamal (Recent Patents on Materials Science, 2014)
The state-of-the-art Nafion® membrane suffers from several shortcomings such as high cost, water dependent conductivity and loss of efficiency at elevated temperature. In contrast particulate filled Nafion® and other nanocomposite polymer electrolyte membranes (PEMs) offer combination of several attractive properties such as high water retention capacity, dimensional, thermal and mechanical stability, excellent conductivity, durability and resistance to fuel cross-over. In this study several research papers and patents related to chemical modification of fillers, different fabrication methods and functional properties of several particulate filled nanocomposite membranes are discussed concisely. The mechanism and role of different particulate fillers in achieving the superior performance of membrane have been demonstrated scientifically. Solution casting, sol-gel, in situ impregnation and self-assembly are common approaches employed for synthesis of nanocomposite PEMs. The functional properties of silica, titania, zirconia, clay, and zeolite hygroscopic fillers filled PEMs in particular are reviewed in details with respect to fuel cell membrane applications.
Keywords: polymer electrolyte membrane